1999
DOI: 10.1128/cdli.6.1.105-114.1999
|View full text |Cite
|
Sign up to set email alerts
|

Angiocentric CD3+T-Cell Infiltrates in Human Immunodeficiency Virus Type 1-Associated Central Nervous System Disease in Children

Abstract: A significant proportion of brain tissue specimens from children with AIDS show evidence of vascular inflammation in the form of transmural and/or perivascular mononuclear-cell infiltrates at autopsy. Previous studies have shown that in contrast to inflammatory lesions observed in human immunodeficiency virus type 1 (HIV-1) encephalitis, in which monocytes/macrophages are the prevailing mononuclear cells, these infiltrates consist mostly of lymphocytes. Perivascular mononuclear-cell infiltrates were found in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Disturbances in oxidative metabolism resembling hypoxia-ischemia may be the consequence of vascular factors and/or the production of toxic metabolites typically associated with hypoxia-ischemia. Inflammatory damage of the vessel wall, endothelium, and bloodbrain barrier by T cells and monocytes is tantamount to a vasculitic state, reminiscent of the angiocentric T-cell infiltrates in human immunodeficiency virus type 1-associated CNS disease (197). The latter, compounded by edema and disturbance of the cerebral microcirculation, may culminate in variably pronounced hypoxic-ischemic injury causing damage to myelin, axons, and oligodendrocytes (227).…”
Section: Comparative Neuropathology Of Tmev-induced Demyelinating Dismentioning
confidence: 99%
“…Disturbances in oxidative metabolism resembling hypoxia-ischemia may be the consequence of vascular factors and/or the production of toxic metabolites typically associated with hypoxia-ischemia. Inflammatory damage of the vessel wall, endothelium, and bloodbrain barrier by T cells and monocytes is tantamount to a vasculitic state, reminiscent of the angiocentric T-cell infiltrates in human immunodeficiency virus type 1-associated CNS disease (197). The latter, compounded by edema and disturbance of the cerebral microcirculation, may culminate in variably pronounced hypoxic-ischemic injury causing damage to myelin, axons, and oligodendrocytes (227).…”
Section: Comparative Neuropathology Of Tmev-induced Demyelinating Dismentioning
confidence: 99%
“…Although not prevalent in adult patients with AIDS, angiocentric mononuclear cell infiltrates have been found at autopsy in the brains of up to 40% of HIV‐1‐infected children [4–6,14–18]. Sharer et al .…”
Section: Introductionmentioning
confidence: 99%
“…Katsetos et al . [18] reported angiocentric (perivascular and in certain cases also transmural) mononuclear cell infiltrates in brain tissue specimens collected at autopsy from five of six children with AIDS. Immunohistochemical studies demonstrated that these angiocentric infiltrates mostly consisted of CD3+ CD8+ CD45RO+ T cells and of CD68+ monocyte/macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mimicry (cross-recognition of common epitomes on HIV-1 and the host protein) was suggested as a mechanism for the endothelial cell injury, the ensuing vasculopathy, and the subsequent ischaemic stroke in these children. 47 Inflammatory markers correlated with common carotid intima-media thickness in young adults with perinatally acquired HIV-1 infection, considered an increased risk for stroke, and further support an inflammation mediated mechanism. 46…”
Section: Hiv-associated Cerebral Vasculopathymentioning
confidence: 73%
“…47 Perivascular and transmural infiltrates of inflammatory cellspredominantly CD3+ and CD8+ T-cellswere detected, with no clinical or immunohistochemical evidence of opportunistic viral infections. 47 The authors proposed that the CD3+ T-cell infiltrates in the CNS of children infected with HIV may represent oligoclonal expansion of cytotoxic T-cells in the context of a vigorous anti-HIV-1 response, even though the viral loads in the CNS during this T-cell perivasculitis were low, raising the possibility of an autoimmune basis for the T-cell response. Molecular mimicry (cross-recognition of common epitomes on HIV-1 and the host protein) was suggested as a mechanism for the endothelial cell injury, the ensuing vasculopathy, and the subsequent ischaemic stroke in these children.…”
Section: Hiv-associated Cerebral Vasculopathymentioning
confidence: 93%